Acute saline expansion increases nephron filtration and distal flow rate but maintains tubuloglomerular feedback responsiveness: role of adenosine A(1) receptors - Blantz, Roland C. (American Physiological Society, 2012)
Temporal adaptation of tubuloglomerular feedback (TGF) permits readjustment of the relationship of nephron filtration rate [single nephron glomerular filtration rate (SNGFR)] and early distal tubular flow rate (V(ED)) while maintaining TGF responsiveness. We used closed-loop assessment of TGF in hydropenia and after acute saline volume expansion (SE; 10% body wt over 1 h) to determine whether 1) temporal adaptation of TGF occurs, 2) adenosine A(1) receptors (A(1)R) mediate TGF responsiveness, and 3) inhibition of TGF affects SNGFR, V(ED), or urinary excretion under these conditions. SNGFR was evaluated in Fromter-Wistar rats by micropuncture in 1) early distal tubules (ambient flow at macula densa), 2) recollected from early distal tubules while 12 nl/min isotonic fluid was added to late proximal tubule (increased flow to macula densa), and 3) from proximal tubules of same nephrons (zero flow to macula densa). SE increased both ambient SNGFR and V(ED) compared with hydropenia, whereas TGF responsiveness (proximal-distal difference in SNGFR, distal SNGFR response to adding fluid to proximal tubule) was maintained, demonstrating TGF adaptation. A(1)R blockade completely inhibited TGF responsiveness during SE and made V(ED) more susceptible to perturbation in proximal tubular flow, but did not alter ambient SNGFR or V(ED). Greater urinary excretion of fluid and Na(+) with A(1)R blockade may reflect additional effects on the distal nephron in hydropenia and SE. In conclusion, A(1)R-independent mechanisms adjust SNGFR and V(ED) to higher values after SE, which facilitates fluid and Na(+) excretion. Concurrently, TGF adapts and stabilizes early distal delivery at the new setpoint in an A(1)R-dependent mechanism.